2001
DOI: 10.1023/a:1008354909478
|View full text |Cite
|
Sign up to set email alerts
|

Use of the ratio of time to progression following first- and second-line therapy to document the activity of the combination of oxaliplatin with 5-fluorouracil in the treatment of colorectal carcinoma

Abstract: This study demonstrates the utility of the GMI as a tool for assessing the activity of novel second-line therapeutic programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Although our data are observational and the statistical analysis that could be performed was limited, we noted an overall link between apparent clinical benefit and increases in PFS ratios. The PFS ratio is a new endpoint that is still debated in the literature [ 17 ] and may be vulnerable to ascertainment bias [ 14 ] but has been shown to give an indication of treatment effect in clinical studies where patients act as their own controls [ 13 , 18 , 19 ]. Our observations concur with these results.…”
Section: Discussionmentioning
confidence: 99%
“…Although our data are observational and the statistical analysis that could be performed was limited, we noted an overall link between apparent clinical benefit and increases in PFS ratios. The PFS ratio is a new endpoint that is still debated in the literature [ 17 ] and may be vulnerable to ascertainment bias [ 14 ] but has been shown to give an indication of treatment effect in clinical studies where patients act as their own controls [ 13 , 18 , 19 ]. Our observations concur with these results.…”
Section: Discussionmentioning
confidence: 99%
“…Scatter plot of T 2 against T 1 for the data from a trial reported by Bonetti et al and reconstructed from Figure of Kovalchik and Mietlowski . Dotted line represents line of T 2 = T 1 …”
Section: Examplementioning
confidence: 99%
“…The data from a trial reported by Bonetti et al is used to illustrate study designs using proposed methods. In the trial, treatment efficacy was assessed by GMI for a second‐line therapy (combination of LV‐modulated 5‐FU and oxaliplatin) in patients with advanced colon carcinoma after failure of a first‐line chemotherapy (LV‐modulated 5‐FU or raltitrexed).…”
Section: Examplementioning
confidence: 99%
See 1 more Smart Citation
“…Time to further tumour progression (TTP 2 ) was evaluated from the date of study entry to the date of documented progressive disease. The TTP 2 /TTP 1 ratio was calculated to obtain the growth modulation index (GMI) (Von Hoff, 1998;Bonetti et al, 2001). Probability of progression-free and overClinical L-OHP+TOM+LFA/FU in advanced colorectal cancer P Comella et al all survival was calculated with actuarial method from the date of accrual to the date of progression, death, or last follow-up, respectively (Kaplan and Meier, 1958).…”
Section: Statistical Consideration and Sample Sizementioning
confidence: 99%